The clinical significance of statins-macrolides interaction: comprehensive review of in vivo studies, case reports, and population studies - Abu Mellal A; Hussain N; Said ASA (Dove Medical Press, 2019)
Abdallah Abu Mellal,1 Nadia Hussain,2 Amira SA Said21College of Health and Human Sciences, Charles Darwin University, Darwin, Northern Territory, Australia; 2College of Pharmacy, Al Ain University of Science and Technology, Al Ain, UAEAbstract: The objectives of this article were to review the mechanism and clinical significance of statins-macrolides interaction, determine which combination has the highest risk for the interaction, and identify key patients’ risk factors for the interaction in relation to the development of muscle toxicity. A literature review was conducted in PubMed and Embase (1946 to December 2018) using combined terms: statins – as group and individual agents, macrolides – as group and individual agents, drug interaction, muscle toxicity, rhabdomyolysis, CYP3A4 inhibitors, and OAT1B inhibitors, with forward and backward citation tracking. Relevant English language in vivo studies in healthy volunteers, case reports, and population studies were included. The interaction between statins and macrolides depends on the type of statin and macrolide used. The mechanism of the interaction is due to macrolides’ inhibition of CYP3A4 isoenzyme and OAT1B transporter causing increased exposure to statins. The correlation of this increased statin’s exposure to the development of muscle toxicity could not be established, unless the patient had other risk factors such as advanced age, cardiovascular diseases, renal impairment, diabetes, and the concomitant use of other CYP3A4 inhibitors. Simvastatin, lovastatin, and to lesser extent atorvastatin are the statins most affected by this interaction. Rosuvastatin, fluvastatin, and pravastatin are not significantly affected by this interaction. Telithromycin, clarithromycin, and erythromycin are the most “offending” macrolides, while azithromycin appears to be safe to use with statins. This review presented a clear description of the clinical significance of this interaction in real practice. Also, it provided health care professionals with clear suggestions and recommendations on how to overcome this interaction. In conclusion, understanding the different characteristics of each statin and macrolide, as well as key patients’ risk factors, will enable health care providers to utilize both groups effectively without compromising patient safety.Keywords: drug interaction, rhabdomyolysis, muscle toxicity, HMG-Co A reductase inhibitors, CYP3A4 inhibitors, OATP1B inhibitors